BIMBINGAN BACAAN ALQURAN MELALUI MAJELIS TAKLIM - Syahraeni, Andi (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2023)
The Majelis Taklim is a place for teaching and education in Islamic religion that is highly flexible and not bound by time or location. It is open to people of all ages, social strata, and genders. This flexibility is its strength, enabling it to endure and become the Islamic Education institution closest to the people. Consequently, the Majelis Taklim serves as an alternative educational institution for individuals who may lack the resources, time, funds, and opportunities to acquire religious knowledge or general education through formal channels. The Majelis Taklim holds a significant position as a tool and medium for nurturing religious awareness. It plays a crucial role in explaining and promoting the teachings of Islam within the community, which collectively becomes the target audience for Islamic outreach efforts. It operates as a self-standing and self-disciplined entity that organizes and implements various activities based on community consensus (mufakat) to facilitate the smooth execution of religious education in line with the participants' desires. The Majelis Taklim holds a crucial position in the development and instruction of Islam in the community, particularly targeting the audience of Islamic outreach, aiming to educate adult women who may lack knowledge of their faith and proficiency in reading the Quran. Presently, many members of the Islamic community still struggle with Quranic literacy, often due to being preoccupied with worldly matters, neglecting the time for Quranic reading and learning. Reading the Quran is an obligation from childhood, and it is a parental duty to teach it. Parents, being the first educators for their children, should themselves be capable of reading the Quran before imparting this knowledge to their offspring. However, it becomes challenging for parents to teach the Quran to their children if they themselves are unable to read it or are unfamiliar with its letters.